Cost-effectiveness analysis of the use of antibiotics for typhoid fever inpatients in RSUD Bayu Asih Purwakarta - Purkon, Dicki Bakhtiar; Agustin, Himeliya; Widyastiwi, Widyastiwi; Kusmiyati, Mimin; Fadhlillah, Faizah Min (Faculty of Pharmacy, Universitas Pancasila, 2025)
Typhoid fever is an infectious disease caused by Salmonella typhi, commonly treated with antibiotics to promote recovery and prevent complications. This study aimed to evaluate both the therapeutic effectiveness (clinical outcomes such as fever resolution and hospital stay duration) and the cost-effectiveness (economic efficiency of antibiotic use) in inpatients with typhoid fever at RSUD Bayu Asih Purwakarta (Bayu Asih District Hospital, Purwakarta) in 2023. A retrospective descriptive design was applied using 75 medical records from January to December 2023. Results showed that levofloxacin had the highest therapeutic effectiveness, reflected by the shortest hospitalization (3.5 days), whereas ceftriaxone was the most cost-effective, with an Average Cost-Effectiveness Ratio (ACER) of Rp. 194,858.78 per treatment. The Incremental Cost-Effectiveness Ratio (ICER) analysis indicated that the additional cost required for levofloxacin compared to ceftriaxone was disproportionate to the clinical benefit gained. In conclusion, while levofloxacin provides faster recovery, ceftriaxone remains the preferred option considering its superior cost-effectiveness. These findings emphasize the need to balance clinical outcomes and economic efficiency when determining antibiotic policies for typhoid management.